Planning Innovation for Implementing Modular Prefabricated Construction in Housing Development in Indonesia Using A Risk-Based ISO 56002:2019 Approach to Improve Project Performance - Rahman, Deansa Agya; Latief, Yusuf (Smart City, 2024)
The development of housing in Indonesia, growing rapidly due to urbanization and population growth, faces challenges in terms of land, labor, and housing backlog. Despite being innovative, modular prefabrication methods are limited by unattractive designs and high costs, slowing down construction, harming the productivity of construction companies, and hindering the growth of the national construction sector. These challenges are prevalent in various countries and are influenced by low knowledge, conservative mindsets, and inhibiting regulations. In Indonesia, additional issues include a lack of mastery of modular prefabrication methods and awareness of long-term benefits. This research identified innovative risk-based applications of modular prefabrication with an ISO approach to improve project performance. The methodology employed includes a literature review, a questionnaire survey, and phased expert validation. The study found that out of 38 risk factors based on the 4 processes of implementing modular prefabrication methods, the average risk assessment is high. As a result, 5 innovations are proposed as efforts to reduce risk assessments. The research analyzed data from various literature, resulting in low inter-data connectivity. However, the processes and outcomes of this research can be relied upon for further understanding in subsequent research. This study combined proposed new innovations with those from external literature that have the potential to be applied in Indonesia for optimizing the cost efficiency of modular prefabrication methods.